Pendekatan Biblika terhadap Kebenaran dan Inspirasi Firman dalam membahas ‘Teologi Kristen Progresif’ dan Implikasinya bagi Pertumbuhan Gereja Masa Kini - Anita Mariana Parulian; Jonatan Octavianus; Hasanema Wau (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study examines the biblical approach to the truth and inspiration of the Word of God in critical dialogue with Progressive Christian Theology (PCT). Using a qualitative-descriptive method and comparative biblical-theological analysis, the research explores the fundamental differences, points of convergence, and potential integration between the two approaches. PCT emphasizes the importance of socio-cultural context, moral development, and human experience in understanding faith. In contrast, biblical theology affirms the authority and unchanging nature of the Word of God as the foundation of absolute truth that undergirds church doctrine and practice. The findings indicate an urgent need to formulate a balanced synthesis between fidelity to the biblical text and sensitivity to contemporary cultural changes. This integrative approach is not intended to weaken the authority of Scripture but to enrich theological understanding so that it becomes more relevant to modern contexts without neglecting divine truth. This synthesis ultimately produces a model of church growth that is contextual, Scripture-centered, and capable of balancing love and truth in addressing contemporary theological, social, and ethical challenges. The model bears significant implications for shaping congregational spirituality, developing pastoral ministry, and guiding the church’s mission amid increasingly complex cultural shifts.